Nanoallergens: A multivalent platform for studying and evaluating potency of allergen epitopes in cellular degranulation. Issue 9 (May 2016) - Deak, Peter E; Vrabel, Maura R; Pizzuti, Vincenzo J; Kiziltepe, Tanyel; Bilgicer, Basar
Degranulation caused by type I hypersensitivity (allergies) is a complex biophysical process, and available experimental models for studying relevant immunoglobulin E binding epitopes on allergen proteins lack the ability to adequately evaluate, rank, and associate these epitopes individually and with each other. In this study, we propose a new allergy model system for studying potential allergen epitopes using nanoallergens, liposomes modified to effectively display IgE binding epitopes/haptens. By utilizing the covalently conjugated lipid tails on two hapten molecules (dinitrophenol and dansyl), hapten molecules were successfully incorporated into liposomes with high precision to form nanoallergens. Nanoallergens, with precisely controlled high-particle valency, can trigger degranulation with much greater sensitivity than commonly used bovine serum albumin conjugates. In rat basophil leukemia cell experiments, nanoallergens with only 2% hapten loading were able to trigger degranulation in vitro at concentrations as low as 10 pM. Additionally, unlike bovine serum albumin-hapten conjugates, nanoallergens allow exact control over particle size and valency. By varying the nanoallergen parameters such as size, valency, monovalent affinity of hapten, and specific IgE ratios, we exposed the importance of these variables on degranulation intensity while demonstrating nanoallergens' potential for evaluating both high- and low-affinity epitopes. The data presented in this article establish nanoallergen platform as a reliable and versatile allergy model to study and evaluate allergen epitopes in mast cell degranulation.